Antimicrobial Susceptibility of Neisseria gonorrhoeae Isolated in Bangladesh (1997 to 1999): Rapid Shift to Fluoroquinolone Resistance - Rahman, Motiur (American Society for Microbiology, 2002)
Periodic monitoring of antimicrobial susceptibility of Neisseria gonorrhoeae is essential for early detection of emergence of drug resistance. A total of 343 gonococcal strains isolated from high-risk and general populations in Bangladesh from 1997 to 1999 were studied. The MICs of penicillin, tetracycline, ciprofloxacin, ceftriaxone, and spectinomycin for the isolates were determined by the agar dilution method. Of the isolates from 1997, 9% were resistant (MIC ≥ 1.0 μg/ml) to ciprofloxacin, while 41 and 49% of the isolates from 1998 and 1999, respectively, were resistant to ciprofloxacin. Of the N. gonorrhoeae isolates from 1998 and 1999, 1.2 and 3.6%, respectively, both were penicillinase producing and displayed plasmid-mediated tetracycline resistance.